Laparoscopic resection of a hepatic mucinous cystic neoplasm: A case report. (2016) - Obara, Shinsaku; Nomi, Takeo; Yamato, Ichiro; Hokuto, Daisuke; Yasuda, Satoshi; Nishiwada, Satoshi; Kawaguchi, Chihiro; Yoshikawa, Takahiro; Yamada, Takatsugu; Kanehiro, Hiromichi; Nakajima, Yoshiyuki
Highlights: The first report of a hepatic mucinous cystic neoplasm (MCN-H) completely resected by laparoscopy. MCN-H has been reported to have the potential for malignancy, and recommended to resection. Benign liver lesions including MCN-H are commonly observed in young females and lacparoscopic liver resection might have cosmetic advantages for patients. Abstract: Introduction: We aimed to present a case of hepatic mucinous cystic neoplasm (MCN-H) that was completely resected by laparoscopy. Presentation of case: A 47-year-old female exhibited mild elevation of serum liver enzyme levels. Abdominal computed tomography revealed a 45-mm multilocular cystic tumor in segment IV of the liver, along with intermittent border calcification and minimal wall thickness. Magnetic resonance imaging revealed fluid-to-fluid level in the cystic tumor, thereby increasing the suspicion of a mild hemorrhage. The patient underwent laparoscopic liver resection (LLR) with a diagnosis of suspected mucinous cystic neoplasm of the liver. The entire tumor was successfully resected with a laparoscopic approach. The resected specimen was a 4.2 × 3.3 × 2.2-cm cystic tumor. Histological findings revealed mucin-producing singular epithelium and ovarian-like stroma. The tumor was diagnosed as a MCN-H with no malignancy. Discussion: This is the first report in which a MCN-H was completely resected by laparoscopy. MCN-H is rare and is observed in only <5% of liver cystic tumors. MCN-H has been reported to have the malignant potential. And complete resection might be a good treatment option. Along with technical development, LLR has been indicated for benign liver tumors to date. Benign liver tumors are commonly observed in young females. The smaller incisions of the laparoscopic approach might provide cosmetic advantages for patients. Conclusion: We presented the first case of a MCN-H completely resected by laparoscopy. Benign tumors and tumors with malignant potential might be good indications for a laparoscopic surgery.